The Exegetical Reception of Imām al-Tirmidhī’s al-Shamā’il al-Muḥammadiyyah in Indonesian Cybermedia - Subkhani K Dewi; Muhamamd Fikri Lubis (UIN Sunan Kalijaga Yogyakarta, 2026)
Al-Shamāʾil al-Muḥammadiyyah is one of the most significant sources of Prophetic history. The book’s popularity is indisputable, spanning from classical traditional discussions to its development in the digital realm. This interdisciplinary study examines the recent transmission of al-Shamāʾil disseminated through cyberspace, employing the concept of exegetical ḥadith reception. The question spans from how videos cover and reach the audience to how the Indonesian ulama explores al-Shamāʾil complex settings and local direct audience. These all are examined through online observation of Indonesian ulama playlist videos on al-Shamāʾil al-Muḥammadiyyah. The results indicate that the study of al-Shamāʾil in Indonesia has shifted from traditional teacher-led classrooms to decentralized digital networks such as YouTube. These digital platforms treat sacred third-century texts both as in-depth scholarly resources and as quick-access information for the masses, creating a unique tension between viral popularity and academic rigor. While scholars have successfully adapted these teachings into practical daily guidance for millions, the current one-way nature of online videos still lacks the deep personal connection characteristic of traditional face-to-face learning.